TARKĪB IḌĀFIY DAN TARKĪB NA‘TIY DALAM KITAB SILSILAT TA‘LĪM AL-LUGHAT AL-‘ARABIYYAH AL-MUSTAWA AL-ṠĀLIṠ AL-TA‘BĪR (ANALISIS SINTAKSIS) - Nuriyah, Sinta; Busri, Hasan; Kuswardono, Singgih (Lisanul Arab: Journal of Arabic Learning and Teaching, 2024)
For Arabic language learners, tarkīb iḍafiy and tarkīb na'tiy are still difficult to distinguish when they are included in a sentence, especially if the sentence does not have a syakkal. In the research of Fauziah et al. who analyzed Nahwu's mistakes in reading Bald Arabic texts, found Nahwu's mistakes in several rules, including Tarkib Iḍafiy and Tarkīb Na'tiy. Therefore, both are important to research. The aim of this research is to determine the type, syntactic function and grammatical markers of tarkīb iḍafiy and tarkīb na'tiy in the book Silsilat Ta'līm Al-Lughat Al-'Arabiyyah Al-Mustawa Al-Ṡāliṡ Al-Ta'bīr. This research is qualitative research with a library research design. The research data is in the form of tarkīb iḍafiy and tarkīb na'tiy in the book Silsilat Ta'līm Al-Lughat Al-'Arabiyyah Al-Mustawa Al-Ṡāliṡ Al-Ta'bīr. Data collection uses documentation techniques and then samples are taken. Next, it was analyzed using research instruments in the form of data cards and recapitulation sheets. The research results show that there are 611 data. However, based on the data collection technique used, namely purposive sampling, only 100 data samples were taken for research. based on type, researcher found 8 iḍafah lafẓiyyah and 46 iḍafah ma'nawiyyah and 46 na'at haqiqiy. Based on its syntactic function, in muḍaf there are 4 fāil data, 6 mubtada' data, 1 khabar data, 7 tābi' data, 7 maf'ūl bih data, 11 maf'ūl fih data, 1 mustaṡna data, 1 isim inna data, 2 data munāda, and 14 majrūr bi al-harfi data. Then, in man'ūt the researcher found 1 fāil data, 1 khabar data, 1 isim kāna data, 12 tābi' data, 7 maf'ūl bih data, 1 khabar kāna data, 15 majrūr bi al-harfi data, and 7 muḍaf ilaih data. Furthermore, based on i'rab and its grammatical markers, in muḍaf the researcher found 14 rafa' data with ḍummah, 23 naṣab data; 22 data with fatḥah, 1 data with alif and 17 data jar with kasrah. Meanwhile, in man‘ūt there are 8 rafa‘ data with ḍummah, 12 naṣab data with fatḥah, and 26 jar data; 25 data with kasrah and 1 data with fatḥah.